Projeto gráfico de livros didáticos da educação de jovens e adultos: análise sob a perspectiva dos docentes de escolas de Bauru (SP) e de Avaré (SP) - Andrade Neto, Mariano Lopes de [UNESP] (2016)
Textbook is an important and comprehensive research field. To discuss it, we have to consider diferentes areas of knowledge, players and users. The studies analyse the most diverses aspects of the subject (textual and visual content, their design, production, dissemination, use and impact on society) on differents perspectives (pedagogical, historical, political, social, economic and material). It is a complex research theme, even when considering an specific focus, as in the case of teaching resources of Youth and Adult Education (Educação de Jovens e Adultos - EJA). EJA is a modality of basic education on its primary and secondary stages, and the National Program of Textbooks for EJA (Programa Nacional do Livro Didático da Educação de Jovens e Adultos - PNLDEJA) attend the Brasilians who did not have access to primary school at the appropriate age. The Education Ministry began PNLDEJA on school year 2008. PNLDEJA aims to distribute textbooks and promote the graphic quality of these books, a task that demands the knowledge of their users and a critical analysis and selection of books. This attitude is not always observed, considering that many graphic designs still looks similar to those developed for the textbooks of child education. This research aims to investigate the evaluation criteria of graphic designs in the EJA Textbook Guide in order to propose recommendations for future programs; it is considered that the discussions of design include the construction of the visual message. Therefore, the thesis is organized in three stages: theoretical research, field research and presentation of results. This is considered a theoretical and practical research, in which there are ascertained information about the knowledge and familiarity of teachers with the graphic design evaluation of EJA textbooks. Through this research, developed with the participation of educators, we propose to revise the current graphics criteria of PNLDEJA to analyze future projects of these books.